Ayurvedic Management Of Duodenal Ulcer: A Clinical Case Study (Prakriti - The International Multidisciplinary Research Journal, 2025)
Duodenal ulcer, a type of peptic ulcer disease, is characterized by an open sore in  the lining of the duodenum—the first part of the small intestine—primarily caused  by excessive gastric acid secretion, Helicobacter pylori infection, or prolonged use  of NSAIDs, leading to symptoms such as epigastric pain, acidity, and indigestion.  This case study evaluates the integrative management of a 31-year-old male  patient diagnosed with a duodenal ulcer, who presented to Jeena Sikho Lifecare  Limited Hospital, Ambala, Haryana, India with chief complaints of gastritis and  hyperacidity persisting for over five years. The patient had a history of alcohol  consumption and exhibited elevated bilirubin levels upon initial evaluation. A  holistic Ayurvedic treatment protocol was initiated, which included classical  Ayurvedic formulations for their cooling and demulcent effects. A strict Pitta shamana diet was also advised. After Ayurvedic intervention, the patient reported  significant symptomatic relief, including the resolution of gastritis and hyperacidity.  Objective findings supported clinical improvement, with total bilirubin decreasing  from 1.58 mg/dL to 0.98 mg/dL and corresponding improvements in direct and  conjugated bilirubin levels, indicating better hepatic function. USG findings  also demonstrated abdominal improvement. This case highlights the potential  of Ayurvedic therapies in managing duodenal ulcers effectively. While results are  promising, further large-scale and controlled studies are necessary to validate these  outcomes and standardize treatment protocols.
Keywords: Duodenal ulcer; Ayurveda; Gastritis; Hyperacidity; Amlapitta; Amashaya; Fatty liver; Yakrit Roga